Efficacy and safety of ozone injection into the intervertebral foramen for treating patients with chronic, intractable postherpetic neuralgia: a one-year follow-up study - Jiang-Lin Wang; Jiang-Lin Wang; Hai-Li Li; Xiang-Bo Liu; Jia-Gui Zhao; Dong Huang; Cheng Wu; Jia-Shuang Wang; Jia-Shuang Wang; Jun Chen; Jun Chen (Frontiers in Neurology)
IntroductionChronic intractable postherpetic neuralgia (PHN) is a significant sequel of herpes zoster and significantly impacts patients’ quality of life. Although some pharmacotherapies, interventional approaches, and neural modulation have been recommended as clinical options, their efficacy is limited. Here, we reported the efficacy and safety of a standardized therapeutic approach with CT-guided intervertebral foramen injection of ozone (IVFO) in patients with chronic intractable thoracic and lumbar (PHN) (n = 56) who had been tolerant or insensitive to first-line drugs, such as gabapentin (GBP) or pregabalin.MethodsVisual analogue scale (VAS), quantitative sensory testing (von Frey filaments only), and infrared thermography were used to identify and quantify the pain intensity, area of mechanical hyperalgesia, and skin temperature in the included patients with PHN before and after IVFO treatment. Moreover, the dosage of and the time to discontinue GBP and complications were also documented after discharge from hospitals.ResultsIn this 1 year follow-up study, the primary endpoint outcomes measured by VAS showed that IVFO treatment resulted in significant relief of spontaneous pain by 59.19% [2.67 ± 0.66] for immediate, 68.18% [2.08 ± 0.89] for half year and 70.79% [1.91 ± 1.19] for 1 year after discharge vs. admission, dramatic decrease in spatial area of mechanical hyperalgesia by 52.35% [3.11 ± 0.70] for immediate and 87.41% [0.82 ± 0.50] for half year after discharge vs. admission and skin temperatures by 63.01% [0.85 ± 0.35] for immediate after discharge vs. admission. Moreover, half of the patients stopped taking GBP 3 months after discharge. No serious complications were reported during the one-year follow-up after IVFO treatment.ConclusionThese results suggest that CT-guided IVFO treatment is a safe and effective interventional approach for the relief of chronic, drug-resistant, thoracic and lumbar PHN.